Incidence of prematurity and associated risk factors among users of a health insurance company - Jolline Lind; Marcelo de Paula Loureiro; Jaime Luis Lopes Rocha (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the incidence ofprematurity in users of a health insurance plan; to analyze the associated risk factors. Methods: a retrospective study was conducted in five maternity hospitals with puerperal women who were users of health insurance plans by telephone interviews guided by a semi-structured questionnaire. The variables studied were related to sociodemographic, clinical and outcome conditions. Univariate and multivariate analysis with Backward logistic regression was performed. Results: 1,193 participants were evaluated and 116 premature births were identified. It was found that preterm birth (p<0.001; OR=4.596; CI95%=2.544-8.305), oligohydramnios (p=0.019; OR=2.697; CI95% =1.140-6.380), diabetes mellitus prior to pregnancy (p<0.001; OR=4.897; CI95%=2.147-11.169), twin pregnancy (p<0.001; OR=7.115; CI95%=3.578-14.148), autoimmune disease (p<0.001; OR=3.799; CI95%=1.987-7.260), stress during pregnancy (p=0.026; OR=1.568; CI95%=1.053-2.335), urinary infection (p=0.008; OR=1.825; CI95%=1.161-2.867), placenta previa (p=0.001; OR=3.180; CI95%=1.517-6.667), pre-eclampsia (p<0.001; OR=4.833; CI95%=2.860-8.169), gestational bleeding (p=0.001; OR=2.185; CI95%=1.340-3.564), interval between pregnancies less than six months (p=0.001; OR=3.502; CI95%=1.594-7.698), pregnancy resulting from in vitro fertilization (p<0.001; OR=2.874; CI95%=1.466-5.637) were statistically relevant as risk factors for prematurity. Conclusion: knowledge of these factors may be important in developing strategies to improve the assistance offered to pregnant women by the health insurance providers.